Changes and Clinical Significance of PIVKA-II in Hepatitis E Patients - Youran Chen; Yanyan Yang; Shanshan Li; Minghao Lin; Xueting Xie; Huifang Shi; Yuchun Jiang; Sijie Zheng; Hui Shao; Naibin Yang; Mingqin Lu (Frontiers Media S.A., 2022)
Increased protein induced by vitamin K absence or antagonist-II (PIVKA-II) levels had been widely reported in patients with hepatocellular carcinoma (HCC) and chronic hepatitis. However, the role of PIVKA-II in hepatitis E is unclear. The aim of this study was to clarify the changes related with PIVKA-II and its clinical significance in hepatitis E. We enrolled 84 patients with hepatitis E hospitalized in two hospitals from December 2019 to June 2021. The levels of serum PIVKA-II and related serological indicators in the patients were determined to elucidate the role of PIVKA-II in hepatitis E. We observed that 59.51% (50/84) of patients showed an increase in PIVKA-II levels. Compared with the normal PIVKA-II group (<32 mAU/L), patients in the elevated PIVKA-II group (>32 mAU/L) had much higher serum total bilirubin (TBIL), direct bilirubin (DBIL), indirect bilirubin (IBIL), and total bile acid (TBA) levels (p < 0.05 for each). Compared with the slightly elevated PIVKA-II group (32-125 mAU/L), patients in the significantly elevated PIVKA-II group (>125 mAU/L) had much lower serum albumin, alanine aminotransferase (ALT), aspartate transaminase (AST) levels, and longer days for the hospital stay (p < 0.05 for each). The association of PIVKA-II with TBIL and DBIL was an inverted U-shaped curve with an inflection point at 199.1 mAU/L). The association of PIVKA-II with IBIL was a U-shaped curve with an inflection point at 18.6 mAU/L while the association of PIVKA-II with albumin was an inverted U-shaped curve with an inflection point at 18.6 mAU/L. With the improvement of the disease, PIVKA-II levels were gradually decreased and finally returned to normal. This trend was consistent with that of bilirubin, and a peak appeared in the third week. Therefore, findings from our study show that the increase in PIVKA-II levels can be related to the degree of hepatic insufficiency in patients with hepatitis E, wherein PIVKA-II levels are transiently increased, and the trend of change can be related to the disease course.